Ultra-stiff large-area carpets of carbon nanotubes. Issue 23 (31st May 2016) - Meysami, Seyyed Shayan; Dallas, Panagiotis; Britton, Jude; Lozano, Juan G.; Murdock, Adrian T.; Ferraro, Claudio; Gutierrez, Eduardo Saiz; Rijnveld, Niek; Holdway, Philip; Porfyrakis, Kyriakos; Grobert, Nicole
Abstract : Herewith, we report the influence of post-synthesis heat treatment (≤2350 °C and plasma temperatures) on the crystal structure, defect density, purity, alignment, dispersibility and mechanical properties of free-standing large-area (several cm 2 ) carpets of ultra-long (several mm) vertically aligned multi-wall carbon nanotubes. Abstract : Herewith, we report the influence of post-synthesis heat treatment (≤2350 °C and plasma temperatures) on the crystal structure, defect density, purity, alignment and dispersibility of free-standing large-area (several cm 2 ) carpets of ultra-long (several mm) vertically aligned multi-wall carbon nanotubes (VA-MWCNTs). VA-MWCNTs were produced in large quantities (20–30 g per batch) using a semi-scaled-up aerosol-assisted chemical vapour deposition (AACVD) setup. Electron and X-ray diffraction showed that the heat treatment at 2350 °C under inert atmosphere purifies, removes residual catalyst particles, and partially aligns adjacent single crystals (crystallites) in polycrystalline MWCNTs. The purification and improvement in the crystallites alignment within the MWCNTs resulted in reduced dispersibility of the VA-MWCNTs in liquid media. High-resolution microscopy revealed that the crystallinity is improved in scales of few tens of nanometres while the point defects remain largely unaffected. The heat treatment also had a marked benefit on the mechanical properties of the carpets. For the first time, we report compression moduli as high as 120 MPa for VA-MWCNT carpets, i.e. an order of magnitude higher than previously reported figures. The application of higher temperatures (arc-discharge plasma, ≥4000 °C) resulted in the formation of a novel graphite–matrix composite reinforced with CVD and arc-discharge-like carbon nanotubes.